Low cost textile-grade carbon-fiber epoxy composites for automotive and wind energy applications. (1st October 2020) - Hiremath, Nitilaksha; Young, Stephen; Ghossein, Hicham; Penumadu, Dayakar; Vaidya, Uday; Theodore, Merlin
Abstract: Carbon fiber reinforced polymer composites are highly desirable for automotive and wind energy applications due to advantages associated with weight reduction, high stiffness and strength, durability, and recyclability. The high cost of carbon fiber has been a limiting factor in its widespread adoption in non-aerospace applications. A low cost (estimated < 11 per kg) wide tow (450-600k) carbon fiber derived from textile grade polyacrylonitirile precursor, and hence called Textile Grade Carbon Fiber (TCF) is introduced in this paper. Fundamental aspects of the TCF are discussed along with a detailed characterization of its mechanical properties. Two manufacturing processes relevant to automotive and wind energy applications are considered, namely-compression molding and resin infusion. At various stages the TCF has been compared to commercial non-aerospace 50k carbon fiber composite. Detailed physical and mechanical properties including tensile, flexural, compression, and interlaminar shear properties are reported and compared to non-aerospace carbon fiber composite. The results provide a means for designers and end-users in the automotive and wind energy sector to consider different forms of economical non-aerospace carbon fibers. Graphical abstract: Image 1